Protótipo de um controlador de potência para a otimização de um sistema térmico - Magalhães, Lucas Cesar Costa (2024)
The HVAC system has become a viable strategy to remedy carbon emissions into the atmosphere due to its premise of air renewal. One of the ways to apply this system is within the work environment since an employee's productivity is proportional to the comfort and quality of the environment in which they are located. Furthermore, a feature that improves the efficiency of this system is its temperature programming, benefiting the industry by increasing the range of air conditioning and central options and optimizing energy use, the control is used to turn on or turn off the device when it reaches the desired temperature. Therefore, in this work, a prototype of a power controller for thermal systems was developed, and subsequently, a system controller intended to control the temperature variation of an estimated environment. The prototype circuit consists of a 3rd order low-pass filter in Sallen Key type, a ZMPT101B voltage sensor, an ACS712 current sensor, eight relay modules, and an LM35 temperature sensor. During the tests, it was expected that the system could stabilize through programmed oscillations of the following voltages: 6V, 9V, and 12V, and continue with the estimated power. In addition to implementing the power controller through the circuit described previously, hardware programming was carried out using Python and Arduino languages. The results were positive and satisfactory, during the tests, the system demonstrated excellence in maintaining the desired power throughout the heating process.